Enhanced migration of fibroblasts derived from lungs with fibrotic lesions. Issue 9 (September 1995) - Suganuma, H; Sato, A; Tamura, R; Chida, K
Abstract : BACKGROUND–The migration and proliferation of fibroblasts may be important in the pathogenesis of pulmonary fibrosis. Considerable data are available on the proliferation of fibroblasts, but very few on their migration. METHODS–The migratory activity of fibroblasts obtained from lung biopsy specimens from 11 patients with idiopathic pulmonary fibrosis (IPF) was studied using a 96-well chemotaxis chamber. Fibroblasts from eight normal controls, seven patients with interstitial fibrosis associated with a collagen vascular disease (IP-CVD), and 13 patients with sarcoidosis were also examined. Migratory activity was tested in a serum-free medium in the presence and absence of platelet derived growth factor (PDGF), 30 ng/ml, as a chemoattractant. RESULTS–Migration of fibroblasts from patients with IPF was enhanced in serum-free maintenance medium alone (mean (SD) controls v IPF: 183 (86) v 689 (491) cells/field), and was also enhanced when cells were stimulated by PDGF (controls v IPF: 829 (222) v 1928 (600) cells/field). Fibroblasts from tissues with dense fibrosis had a greater capacity for migration than those from an earlier stage of fibrosis. No correlation was found between migratory activity and proliferative capacity of the individual cells. CONCLUSIONS–The fact that fibroblasts from fibrotic lungs migrate faster than those from controls suggests that migration is related to the initiation of the pulmonary fibrotic process. These in vitro studies suggest that fibroblasts derived from the lungs of patients with pulmonary fibrosis have a migratory phenotype. Such a change in fibroblast phenotype, if it occurred in vivo, may be important in the context of the pathogenesis of pulmonary fibrosis.